ANALISIS PENINGKATAN MINAT BELAJAR SISWA DENGAN MENGGUNAKAN MODEL GAME-BASED LEARNING PADA PEMBELAJARAN MATEMATIKA MATERI PECAHAN KELAS V SDN PW 01 - Zahrotul Khusniah; Yulia Linguistika; Erif Ahdhianto (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article reviews the analysis of students’ interest improvement in learning by using the Game-based learning (GBL) model in fractional learning material of mathematics for class V students at SDN PW 01. The approach used in the study was a mixed-methods with a quasi-experimental with pre-experimental design. Quantitative data were analyzed by using the Wilcoxon Signed Rank Test test with SPSS 16.0 for Windows application. Since the data processed were ordinal-scaled data, data were analyzed by providing non-parametrical statistics and no need to test normality distribution. Whilst the qualitative data were analyzed using narrative analysis. The study was conducted by giving a pretest in the form of a questionnaire on students' interest in fractional learning material of mathematics before using the Game-Based Learning model. Hereafter, giving treatment in the form of fractional learning material of mathematics used the Game-Based Learning (GBL) model through the Quizizz learning application, Kahoot! and Wordwall. After that, a post-test was administered to the students in the form of a questionnaire on students' interest in fractional learning material of mathematics after using the Game-Based Learning model. Based on the results of hypothesis testing were obtained that the significance level of 0.000 meant Ha was accepted and H0 was rejected. In addition, based on the results of interviews that there was an improvement of students' interest in fractional learning material of mathematics, which was carried out by using the Game-based learning (GBL) model. Above all, it could be concluded that there was an improvement on students' interest in fractional learning material of mathematics through the Game-Based Learning (GBL) model for students of class V in SDN PW 01.